2016
DOI: 10.1097/md.0000000000002597
|View full text |Cite
|
Sign up to set email alerts
|

A Large Cohort Study on the Clinical Value of Simultaneous Amplification and Testing for the Diagnosis of Pulmonary Tuberculosis

Abstract: The AmpSure simultaneous amplification and testing method for the detection of Mycobacterium tuberculosis (SAT-TB assay) was designed to diagnose rapidly pulmonary tuberculosis (PTB). Unfortunately, the diagnostic advantage is unclear from previous small sample studies. In the current inquiry, a large sample size was used to reevaluate the clinical accuracy of the SAT-TB assay using sputum specimens.A total of 3608 patients with suspected PTB were enrolled prospectively for diagnosis from sputum specimens usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 12 publications
(13 reference statements)
0
23
0
Order By: Relevance
“…BACTEC MGIT 960 (Becton Dickinson Life Sciences, Franklin Lakes, NJ, USA) was performed according to the standard procedure of the manufacturer (20). SAT-TB was carried out using the method of AmpSure assay (Shanghai Rendu Biotechnology, Shanghai China) following the instructions of the manufacturer (18). LAMP reactions were conducted with Loopamp DNA amplification kit (both from Eiken Chemical, Tochigi, Japan), as previously described (11).…”
Section: Methods Patientsmentioning
confidence: 99%
“…BACTEC MGIT 960 (Becton Dickinson Life Sciences, Franklin Lakes, NJ, USA) was performed according to the standard procedure of the manufacturer (20). SAT-TB was carried out using the method of AmpSure assay (Shanghai Rendu Biotechnology, Shanghai China) following the instructions of the manufacturer (18). LAMP reactions were conducted with Loopamp DNA amplification kit (both from Eiken Chemical, Tochigi, Japan), as previously described (11).…”
Section: Methods Patientsmentioning
confidence: 99%
“…BACTEC MGIT 960 (Becton Dickinson Life Sciences, Franklin Lakes, NJ, USA) was performed according to the standard procedure of the manufacturer [20]. SAT-TB was carried out using the method of AmpSure assay (Shanghai Rendu Biotechnology, Shanghai China) following the instructions of the manufacturer [18]. LAMP reactions were conducted with Loopamp DNA amplification kit (both from Eiken Chemical, Tochigi, Japan), as previously described [11].…”
Section: Examinationsmentioning
confidence: 99%
“…Since RNA is much more unstable than DNA, so SAT-TB assay (SAT-TB) has the advantage of lower false-positive rates and good reproducibility [12]. Previous studies of NAATs have demonstrated superior sensitivity and specificity for the diagnosis of pulmonary TB with sputum specimens [13][14][15][16][17][18]. However, there is still limited data on the performance of NAATs on the diagnosis of TBP with pleural fluid specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Since RNA is much more unstable than DNA, so SAT-TB assay (SAT-TB) has the advantage of lower false-positive rates and good reproducibility (12). Previous studies of NAATs have demonstrated superior sensitivity and specificity for the diagnosis of pulmonary TB with sputum specimens (13)(14)(15)(16)(17)(18). However, there is still limited data on the performance of NAATs on the diagnosis of TBP with pleural fluid specimens.…”
Section: Introductionmentioning
confidence: 99%